First Report of Chlamydia Seroprevalence and Risk Factors in Domestic Black-Boned Sheep and Goats in China - Sun, Li-Xiu; Liang, Qin-Li; Hu, Xiao-Hui; Li, Zhao; Yang, Jian-Fa; Zou, Feng-Cai; Zhu, Xing-Quan (Frontiers in Veterinary Science, 2020)
The Gram-negative bacteria of the genus Chlamydia cause a wide range of diseases in humans and animals. The seroprevalence of Chlamydia in domestic black-boned sheep and goats in China is unknown. In this survey, a total of 481 serum samples were collected randomly from domestic black-boned sheep and goats from three counties in Yunnan province, southwest China from July to August 2017. The sera were examined by an indirect hemagglutination (IHA) test. Antibodies to Chlamydia were detected in 100/481 (20.79%, 95% CI 17.16-24.42) serum samples (IHA titer ≥ 1:64). The Chlamydia seroprevalence ranged from 12.21% (95% CI 7.81-16.61) to 30.89% (95% CI 22.72-39.06) across different regions in Yunnan province, and the differences were statistically significant (P < 0.01). The seroprevalence in male domestic black-boned sheep and goats (28.64 %, 95% CI 22.36-34.92) was significantly higher than that in the females (15.25%, 95% CI 11.05–19.45) (P < 0.01). However, there was no statistically significant difference in Chlamydia seroprevalence in domestic black-boned sheep and goats between ages and species (P > 0.05). To our knowledge, this is the first report of Chlamydia seroprevalence in domestic black-boned sheep and goats in Yunnan Province, southwest China. These data provide baseline information for future implementation of measures to control Chlamydia infection in these animals.